KARAKTERISTIK DAN KEPATUHAN DIET DASH PADA PASIEN HIPERTENSI DIRUANG RAWAT INAP RUMAH SAKIT SANTA ELISABETH TAHUN 2023 - Magda Siringo-ringo; Roberta Mimi Indah Gultom (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Characteristics mean different things about a person, place, or thing that describes them. Compliance, which was originally known as "compliance", has a definition as the extent to which a patient's behavior (in terms of taking medication, following a diet, or making other lifestyle changes) must be appropriate according to clinical prescriptions. the DASH diet (Dietary Approach To Stop Hypertension) which is a vegetable and fruit diet that contains a lot of dietary fiber, which is 30 grams per day and certain minerals, namely potassium, magnesium and calcium while salt intake is limited, which is only 3 grams per day. The research objective was to determine the characteristics and adherence to the DASH diet in hypertensive patients at Santa Elisabeth Hospital Medan in 2023. Research Methods: This type of research is descriptive with a population of 120 hypertensive patients. The sampling technique in this study was random sampling in hypertensive patients with 53 people as a collection instrument. data using a questionnaire with 9 question items. The results of the study: The characteristics of respondents aged 56-60 years were 20 people (37.7%). Most of the female sex as many as 32 people (60.4%). Most of the duration of the patient suffering from hypertension 1-5 years as many as 36 people (67.9%). Most of the respondents to adherence to the hypertension diet found that 15 patients (28.3%) did not feel it. Conclusion: There are 20 people (37.7%) aged 56-60 years. Most of the female sex as many as 32 people (60.4%). Most of the duration of the patient suffering from hypertension 1-5 years as many as 36 people (67.9%). Most of the respondents to adherence to the hypertension diet found that 15 patients (28.3%) did not feel it. Suggestions for people with hypertension respondents are expected to be able to maintain and regulate a balanced diet with the DASH diet information to avoid hypertension.